2003
DOI: 10.1099/jmm.0.05011-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mupirocin E-test for susceptibility testing of Staphylococcus aureus

Abstract: Interpretation of the mupirocin E-test for low-level mupirocin-resistant Staphylococcus aureus strains has been improved by adding the indicator dye tetrazolium. E-tests were compared with agar dilution methods for assessing mupirocin susceptibility. MICs obtained by the agar dilution method and E-tests showed 89·3 % agreement within 2 log 2 dilution criteria. The agreement between MICs increased to 100 % in the 1 log 2 dilution definition when the indicator dye tetrazolium was added to the E-test. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…An MIC falling between 8 and 256 μg/ml was taken a low or intermediate resistance, those showing ≥512 μg/ml as highly resistant and those isolates showing MIC <4 μg/ml were interpreted as sensitive. [ 6 7 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An MIC falling between 8 and 256 μg/ml was taken a low or intermediate resistance, those showing ≥512 μg/ml as highly resistant and those isolates showing MIC <4 μg/ml were interpreted as sensitive. [ 6 7 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 4 5 ] Resistance of MRSA to mupirocin is categorized into two types: Low-level or intermediate resistance (MupI), with MICs of 8-256 μg/ml, and high-level resistance (MupR), with MICs ≥512 μg/ml. [ 6 7 ] A plasmid-mediated mupA gene appears to be associated with high-level resistance, while low-level resistance is associated with chromosomal point mutations. [ 8 9 10 ] Another novel gene, mupB is also responsible for high-level of mupirocin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, methods for testing topical agents have not been included in susceptibility testing documents published by the Clinical and Laboratory Standards Institute (CLSI; formerly NCCLS), although guidelines for testing by various methods have been suggested by others (9,10,12,13,16,17). The British Society for Antimicrobial Chemotherapy has formal recommendations for the testing of mupirocin (www.bsac .org.uk) that include testing of a 5-g and a 20-g mupirocin disk.…”
mentioning
confidence: 99%
“…We analysed a total of 124 S. aureus isolates and found 20 Mup RH , 19 Mup RL and 85 Mup S . We established the criteria using 45 S. aureus strains (16 Mup RH , 16 Mup RL and 13 Mup S ) that had been well characterized by the agar dilution method and PFGE (Santos et al, 1999), PCR (Nunes et al, 1999) and Etest (Mondino et al, 2003). We validated the criteria by analysing another 79 S. aureus nosocomial strains.…”
Section: Discussionmentioning
confidence: 99%
“…The dilution method is considered the 'gold standard' for the determination of mupirocin-resistance levels. We have recently shown that the mupirocin Etest (AB Biodisk) with tetrazolium reduction is more accurate, thus bringing the Etest closer to the gold standard agar dilution method for determining the mupirocin MICs for S. aureus strains (Mondino et al, 2003). However, both agar dilution and Etest are too expensive and laborious for routine application.…”
Section: Introductionmentioning
confidence: 99%